Insect faunal diversity in various agro-ecosystems through light traps in sub-humid ecological zone of Southern Rajasthan - Swami, Hemant; ., Lekha (Indian Journal of Plant Protection, 2020)
Investigations were undertaken to study and record the insect fauna and species spectrum attracted towards the light trap in three ecosystems at Udaipur during Rabi 2014-15. Lepidoptera dominated the catches by light traps contributing 23.27, 29.64 and 32.62 per cent along with Hemiptera (30.80, 29.62 and 25.53%), followed by Diptera (18.80, 19.11 and 22.05%) and Coleoptera (15.50, 12.98, and 13.14%) in pulse, oilseed and vegetable ecosystem, respectively. The Shannon biodiversity index as calculated for cumulative collection of all insect orders and maximum diversity of insect fauna recorded from oilseed ecosystem was 1.648 followed by 1.595 in vegetable and 1.731 in pulse ecosystem.